2023
DOI: 10.3390/s23031577
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Methodology for Estimation of Shoulder Load in Wheelchair-Related Activities Using Wearables

Abstract: There is a high prevalence of shoulder problems in manual wheelchair users (MWUs) with a spinal cord injury. How shoulder load relates to shoulder problems remains unclear. This study aimed to develop a machine-learning-based methodology to estimate the shoulder load in wheelchair-related activities of daily living using wearable sensors. Ten able-bodied participants equipped with five inertial measurement units (IMU) on their thorax, right arm, and wheelchair performed activities exemplary of daily life of MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This study developed a machine learning method to estimate shoulder load in wheelchair-related activities of daily living using wearable sensors. The method was validated using data from 10 ablebodied participants and showed promising results [28]. Human activity recognition (HAR) based on wearable sensor data is a rapidly developing field with many practical applications.…”
Section: Figure 1 Glove System With Multiple Sensors [8]mentioning
confidence: 99%
“…This study developed a machine learning method to estimate shoulder load in wheelchair-related activities of daily living using wearable sensors. The method was validated using data from 10 ablebodied participants and showed promising results [28]. Human activity recognition (HAR) based on wearable sensor data is a rapidly developing field with many practical applications.…”
Section: Figure 1 Glove System With Multiple Sensors [8]mentioning
confidence: 99%
“…In particular, using supervised ML models to circumvent biomechanical models that are computationally expensive has become commonplace. Numerous studies have reported ML applications for generating in vivo insights (e.g., joint and muscle loading) from either OMC or IMC inputs [28][29][30][31][32][33][34][35][36][37][38] or markerless methods [27]. Among ML approaches, deep learning models, including Convolutional Neural Networks (CNN) and, increasingly, Recurrent Neural Networks (RNN), have become popular in lowerextremity biomechanical analyses [26].…”
Section: Introductionmentioning
confidence: 99%